Classification of Quadratic Parastrophically Uncancelable Functional Equations for Five Object Variables on Quasigroups - Koval, R. F. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We continue the investigation of quadratic functional equations over quasigroup operations and prove that every parastrophically uncancelable quadratic equation for five object variables is parastrophically equivalent to one of four given functional equations.